Limnological variations of a deep reservoir in periods with distinct rainfall patterns - Geraldes,Ana Maria (2012)
AIM: This study intends to provide information on how precipitation variation may impact environmental parameters (total phosphorus, water temperature, pH, conductivity, dissolved oxygen, Secchi depth, chlorophyll a and Anabaena abundance) and crustacean zooplankton composition and abundance. METHODS: Samples were collected monthly from October 2000 to September 2002 and from October 2007 to September 2009 at one single sampling station located at the deepest point of the reservoir. All data were obtained in the euphotic zone. RESULTS: The highest values of total phosphorous concentrations were reported together with the maximal values of precipitation. Conversely, conductivity decreased during the wet periods. Anabaena presence was only detected between September and December 2001. Daphnia longispina total abundance showed large inter-annual differences. A clear seasonal pattern was inferred for Diaphanosoma brachyurum and Ceriodaphnia pulchella. Both species are thermophilic and begin to be detected in early summer when the water temperature is around 15 ºC. Copidodiaptomus numidicus abundance did not present a clear seasonal pattern. CONCLUSIONS: Some of the observed shifts in environmental parameters (Conductivity, total phosphorus concentrations and Anabaena abundance) resulting in changes in zooplankton abundance are induced by rainfall variation. The most affected species were those with a lack of seasonality (C. numidicus) or species occurring mainly in winter/early summer (Daphnia longispina). However, a wide range of physical, chemical and biotic interactions is likely to influence zooplankton abundance. Therefore, caution is advised when relating the observed variation exclusively with rainfall intensity. In fact, some of the observed shifts were induced by other factors varying subtly in a seasonal or inter-annual pattern, independently of rainfall intensity.